Participatory evaluation of planted forages in Ada’a, Miesso and Alamata woredas of Ethiopia - Adie, Aberra; Duncan, Alan J.; Ergano, Kebebe (International Livestock Research Institute, 2010)
The IFAD-funded Fodder Adoption Project facilitated local fodder stakeholder platforms in three pilot learning woredas (Ada’a, Mieso and Alamata) starting in May 2008. Through these stakeholder platforms different fodder options were introduced to farmers with the aim of alleviating the feed scarcity problem for enhanced market-oriented livestock production. Through focus group discussions with farmers and other stakeholders, different forage species were selected by farmers to be planted on their farms. Farmers evaluated the performance and impact of the different forages they planted in 2008 and made further choices on which to plant in following years. The results of the initial evaluation process revealed that there were preferences for certain forage species from the various options they tried in their farms. During the second year, the farmers were encouraged to plant the forage species of their preference for further fodder development. Through the activities of the stakeholder platforms successful fodder species and the processes which led to their uptake have been scaled out to new kebeles and farmers in the three woredas. As a result, the number of farmers participating in forage development increased from 44 to 84 in Ada’a, from 40 to 80 in Miesso and remained at 20 in Alamata in both 2008 and 2009 planting seasons. A participatory forage evaluation was carried out in Sept 2010 to understand and document the farmers’ perceptions of the forages they had grown.